2021
DOI: 10.3390/ijms22010471
|View full text |Cite
|
Sign up to set email alerts
|

More Than Just Simple Interaction between STIM and Orai Proteins: CRAC Channel Function Enabled by a Network of Interactions with Regulatory Proteins

Abstract: The calcium-release-activated calcium (CRAC) channel, activated by the release of Ca2+ from the endoplasmic reticulum (ER), is critical for Ca2+ homeostasis and active signal transduction in a plethora of cell types. Spurred by the long-sought decryption of the molecular nature of the CRAC channel, considerable scientific effort has been devoted to gaining insights into functional and structural mechanisms underlying this signalling cascade. Key players in CRAC channel function are the Stromal interaction mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 171 publications
(179 reference statements)
0
12
0
3
Order By: Relevance
“…Cav-1| Caveolin-1 is a protein that seems to have a multitude of functions in the regulation of SOC currents, from the hindrance of SOCE-activation during meiosis, to cell type-specific SOCE activation via the modulation of micro-domains associated with SOCE (for a review on this, see [ 89 ]). Depriving cells of caveolae/caveolin-1 leads to a decrease in viral uptake, viral protein expression, virion release and Cav-1 has been shown to initiate inflammatory reactions by activating leukocytes and nuclear factor-κB [ 90 , 91 ].…”
Section: Calcium Ion Channels and Sars-cov-2mentioning
confidence: 99%
“…Cav-1| Caveolin-1 is a protein that seems to have a multitude of functions in the regulation of SOC currents, from the hindrance of SOCE-activation during meiosis, to cell type-specific SOCE activation via the modulation of micro-domains associated with SOCE (for a review on this, see [ 89 ]). Depriving cells of caveolae/caveolin-1 leads to a decrease in viral uptake, viral protein expression, virion release and Cav-1 has been shown to initiate inflammatory reactions by activating leukocytes and nuclear factor-κB [ 90 , 91 ].…”
Section: Calcium Ion Channels and Sars-cov-2mentioning
confidence: 99%
“…In contrast to the triad, where RyR1 and DHPR do not have a structural function, the MCS containing SOCE are formed by the recruitment of STIM1 to the PM and its binding to Orai1. Several SOCE-interacting proteins were reported, such as SOCE-associated regulatory factor (SARAF), STIM-activating enhancer (STIMATE), partner of STIM (POST), or CRAC regulator 2A (CRACR2A), which serve as fine regulators of Ca 2+ entry (rev in [ 78 ]). To the best of our knowledge, however, none of these regulatory proteins were reported to modulate SOCE in skeletal muscles.…”
Section: Localization and Role Of Soce Molecules In Cells With “Constrained” Architecturementioning
confidence: 99%
“…To date, it is known that, in addition to SARAF, there are several auxiliary proteins which, through direct interactions with STIM1 and/or Orai1, favor or reduce the influx of Ca 2+ . For example, several studies have shown that STIMATE (STIM-activating enhancer), an ER/SR transmembrane protein encoded by the TMEM110 gene, interacts directly with STIM1, favoring the conformational change of STIM1 and contributing to maintaining the correct structure of the ER/SR-PM junctions [39][40][41]. Furthermore, it has been shown that STIMATE depletion reduces the formation of STIM1 points at the ER-junctions [39][40][41].…”
Section: Stim1 Protein: the Ca 2+ Sensor For Socementioning
confidence: 99%
“…For example, several studies have shown that STIMATE (STIM-activating enhancer), an ER/SR transmembrane protein encoded by the TMEM110 gene, interacts directly with STIM1, favoring the conformational change of STIM1 and contributing to maintaining the correct structure of the ER/SR-PM junctions [39][40][41]. Furthermore, it has been shown that STIMATE depletion reduces the formation of STIM1 points at the ER-junctions [39][40][41]. Moreover, in skeletal muscle cells, an alternatively spliced variant of STIM1 is also expressed.…”
Section: Stim1 Protein: the Ca 2+ Sensor For Socementioning
confidence: 99%